Method to measure faciolingual teeth inclination (Mustansiria Dental Journal, 2024)
This research evaluates the faciolingual inclination of people in Mosul city as a basebracket design for straight wire arch technique (SWA) 50 study models (25females) used aged 12-15 years, they concomitant with six keys of normal 52.that suggested by AndrewsThe data then subjected to statistical evaluation at p